2013
DOI: 10.1021/ma401193u
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Control of Helical Structures of an ABC-Type Triblock Terpolymer by Distribution Control of a Blending Homopolymer in a Block Copolymer Microdomain

Abstract: The control of microphase-separated structures in a poly(styrene-block-butadiene-block-methyl methacrylate) (SBM) was investigated in three dimensions by transmission electron microtomography. Neat SBM self-assembled into a double-helical structure of polybutadiene (PB) domains around hexagonally packed core polystyrene (PS) cylinders in a poly(methyl methacrylate) matrix. When PS homopolymer with a lower molecular weight than that of the PS block in SBM was added to the SBM, the PB domains transformed from do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
61
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 37 publications
1
61
0
Order By: Relevance
“…Relatively recent additions to these categories include the Fddd network [ 5,6 ] and the Frank-Kasper σ phase. [ 7 ] Chemical addition of a third dissimilar block to an AB diblock copolymer yields an ABC copolymer, which, depending on block lengths and incompatibilities, can exhibit significantly enriched phase behavior by microphase-ordering into various combinations of the morphologies listed above, [ 2,[8][9][10] as well as morphologies that are unique to ABC copolymers (e.g., the knitting pattern [ 11 ] and twisted helices [ 12,13 ] ).Recent developments regarding charged multiblock copolymers that can form physical networks and exhibit robust mechanical properties herald new and exciting opportunities for contemporary technologies requiring amphiphilic attributes. Due to the presence of strong interactions, however, control over the phase behavior of such materials remains challenging, especially since their morphologies can be solvent-templated.…”
mentioning
confidence: 99%
“…Relatively recent additions to these categories include the Fddd network [ 5,6 ] and the Frank-Kasper σ phase. [ 7 ] Chemical addition of a third dissimilar block to an AB diblock copolymer yields an ABC copolymer, which, depending on block lengths and incompatibilities, can exhibit significantly enriched phase behavior by microphase-ordering into various combinations of the morphologies listed above, [ 2,[8][9][10] as well as morphologies that are unique to ABC copolymers (e.g., the knitting pattern [ 11 ] and twisted helices [ 12,13 ] ).Recent developments regarding charged multiblock copolymers that can form physical networks and exhibit robust mechanical properties herald new and exciting opportunities for contemporary technologies requiring amphiphilic attributes. Due to the presence of strong interactions, however, control over the phase behavior of such materials remains challenging, especially since their morphologies can be solvent-templated.…”
mentioning
confidence: 99%
“…Depending on the copolymer composition, the helical structures can be double-, triple-, and to a lower extent, four-stranded as well as a mixture of them. [44] Although the exact structure cannot be distinguished by TEM, the relatively high volume fraction of PS (Table 1) leads to the assumption that the triple helix predominates. The TEM image of neat ISM (Figure 1a) shows a [63] supporting the Ia3d symmetry of the gyroid morphology.…”
Section: Resultsmentioning
confidence: 99%
“…[42,43] Higuchi et al used blending to observe the passing from a double-to triple-and even to four-stranded helical structure of a SBM triblock terpolymer with a polystyrene core cylinder, by adding continuously small amounts of polystyrene homopolymer. [44] Blending triblock terpolymers with homopolymers was also used to complement phase transition studies. [45] When studying binary blends of AB diblock copolymers, ordered structures different from the expected for neat AB diblock copolymers can be found.…”
Section: Introductionmentioning
confidence: 99%
“…The crystallization of mixtures combining block copolymer with semi-crystalline homopolymers is more complicated than that of homopolymer/homopolymer blends [17][18][19][20]. It was found that PMMA or P2VP almost had no influence on the spherulite size of PVDF but significantly decreased the degree of crystallinity.…”
Section: Introductionmentioning
confidence: 99%